Kalanchoe crop development under different levels of irrigation - Soares, Fátima Cibele; Parizi, Ana Rita Costenaro; Corrêa, Francieli Ribeiro; Bortolás, Francielle Altíssimo; Russi, Jumar Luis (Revista Ceres, 2016)
Despite its importance in the floriculture sector, irrigation management of kalanchoe is characterized by empiricism, being necessary further studies on the use of water by this crop. Thus, the objective of this study is to analyze the several effects of irrigation levels on the growth of kalanchoe crop conducted in greenhouse in the municipality of Alegrete, state of Rio Grande do Sul. The experiment was conducted in a 7 x 15 m protected environment. The experimental design was completely randomized, with four treatments (irrigation levels corresponding to 40, 60, 80 and 100% of the pot water retention capacity - PC) and four repetitions, totaling sixteen plots. The crop cycle was 224 days after transplanting and the applied average depths were: 451.82; 367.38; 282.94; 198.51 mm for treatments: 100; 80; 60 and 40% of PC, respectively. Canopy area and number of leaves per plant were evaluated over the crop cycle. In the end of the cycle, the canopy diameter, number of inflorescences per plant and the number of flowers per plant were evaluated. No significant differences were found only to the canopy area, by the F test. Irrigation water depths between 40 and 70% of the pot capacity were more appropriate for the crop growth in the study region. The cultivar presented the best development at irrigation levels below the maximum vessel water retention capacity, that is, it is resistant to drought.